Educar para crescer: valores para a vida - o papel da família na transmissão de valores na primeira infância - Cacciacarro, Mariana Filippini (2016)
This is a qualitative research with the use of Focus Groups and Grounded Theory as data collection methodology and analysis respectively, which had as general objective to investigate the parental understanding of the concept of values, what values are considered relevant by their point of view and how important are the parents and family in the transmission of values to children during childhood. The study included 25 parents or responsible for at least one child between four and seven years old, enrolled in schools in a mid-sized county of São Paulo state. Their social vulnerability indices ranged between medium and high (SEADE, 2010). After analyze the material we understand that parents and guardians are aware of the values they would like to pass on to their descendants, however they feel insecure because of the changes and the complexity of the society in which we live. They understand that the concept of value is something that we built on relationships and what guide and sustains our conduct . Educating in values is therefore understood as moral education, because the values are responsible to guide people to behave as responsible individuals and to establish a hierarchy between things. Participants believe that the values help the individual to maintain an ethical stance and criticism of the moral, and give them instruments to assume a reflexive attitude to their actions. The study results also point out the need for investment in areas that promote exchanges and dialogues between parents on the subject of values, because although they are common in everyday attitudes, are still a source of doubt and insecurity when related to the educational process